Evaluasi Persepsi Pengguna terhadap Penggunaan Pengenalan Wajah dan GPS untuk Sistem Absensi - Sinaga, Jovanca Blesshery; Valencia, Cindy; Lubis, Muhammad Anggi; Yuanda, Raihan; Devyanti, Kharisma Nur; Rudiansah, Cahya; Purnama, Endang; Indara, Gema Parasti (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
One of the roles of current technology is online attendance recording (e-presence) based on facial recognition and GPS, which was previously dominantly done in the traditional way through paper recording. This manual attendance causes a lot of fraud, such as absentee deposits and forged signatures so that they are not effective in recording them. The purpose of this paper is to provide an analysis related to the exploration of user perception of facial recognition and GPS-based attendance. The method used is of a qualitative type, by analyzing and synthesizing findings from relevant previous research. This research was conducted to help understand technology as a solution to student cheating in absenteeism. Face and location presence use facial recognition features in biometric technology that are able to provide high accuracy, and the implementation of GPS aimed at verifying the user's location. The results of qualitative analysis, facial recognition-based attendance and GPS are effective and practical solutions to overcome fraud in attendance recording.